Seroprevalence of the Respitatory Syncytial Virus in pediatric patients with allergic rhinitis allergic - Julia Arias P.; Yraima Larreal E.; Paola Reyes; María Carrillo C.; Yuselis Briceño R; Nereida Valero C (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2017)
The objective of this study was to determine the prevalence of Respiratory Syncytial Virus (RSV) in pediatric patients with allergic rhinitis (AR). We included 56 patients older than 7 years and younger than 15, with clinical diagnosis of allergic rhinitis (AR). Blood samples were taken without anticoagulants, to obtain serum. IgG anti-RSV and total IgE were determined by the ELISA technique. The results showed that 38 (68%) were schoolchildren and 18 (32%) adolescents, 14 (25%) female and 42 (75%). Of the total number of patients studied, 52 (92.86%) were positive for the presence of IgG anti-RSV antibodies, with a significant overall prevalence, similar prevalence presented by the control group. A significant increase (346.8 ± 264.7 UL / ml) of IgE was observed in patients with RA who were seropositive for RSV compared to the control group without RA (116.3 ± 89.7 UL / ml). The results show a high seroprevalence of RSV in the region, especially in school age, this early infection could be determinant in the secretion of mediators that contribute to the appearance and severity of respiratory diseases such as allergic rhinitis and bronchial asthma. Therefore it is concluded that the quantification of total IgE can be considered as a quality test for the diagnosis and monitoring of allergic rhinitis.